2020
DOI: 10.3329/jafmc.v14i2.45903
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile Pattern in Type 2 Diabetes Mellitus Patients

Abstract: Introduction: Dyslipidemia has been noted to play an integral role in the pathogenesis and progression of micro and macrovascular complications in Diabetes Mellitus (DM) patients. Lipid profile is the indicators of dyslipidemia. Objectives: To evaluate the prevalence and pattern of dyslipidemia in type 2 DM patients. Materials and Methods: This cross sectional study was conducted at Armed Forces Institute of Pathology (AFIP) from November 2014 to October 2015. The study included 300 type 2 diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Although Goel S et al 1 reported that the lipid profile abnormalities were among 83% of the diabetes patients and these findings of lipid profile abnormalities were higher as compared to this study. In another study by Sultana MS et al 16 also found higher frequency of lipid profile abnormalities 94% amongst 300 individuals having type II diabetes who participated in their study.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Although Goel S et al 1 reported that the lipid profile abnormalities were among 83% of the diabetes patients and these findings of lipid profile abnormalities were higher as compared to this study. In another study by Sultana MS et al 16 also found higher frequency of lipid profile abnormalities 94% amongst 300 individuals having type II diabetes who participated in their study.…”
Section: Discussionmentioning
confidence: 72%
“…Consistently, Javed RA et al 15 also reported that the occurrence of dyslipidemia was statistically insignificant according to gender. In the study by Sultana MS et al 16 also observed that there was not significant difference in serum TC, TG and LDL-C according to gender (p->0.05) while HDL was statistically (p-<0.05). Although Goel S et al 1 reported that there were noticeable disparities between the sexes in the prevalence of lipid abnormalities in several aspects of the parameters of lipids, while with the exception of HDL, they did not have a statistically significant association.…”
Section: Discussionmentioning
confidence: 87%
“…Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycemia caused by absolute or relative deficiency of insulin. 1 Diabetes more common worldwide according to this data in the year 2017, 463 million people had diabetes worldwide, the rate of 8.8% among adults, while type 2 diabetes make 90% of cases this data show that the type 2 was very rare than type1 diabetes. Another study shows that the number of patients with diabetes mellitus globally has four times as many in the past three decades.…”
Section: Introductionmentioning
confidence: 73%
“…There is a relationship between lipid profile and the progression of type 2 diabetes mellitus [18]. The study on Diabetic patients found that high levels of total cholesterol (TC), triglycerides(TG), and Low-Density Lipoprotein-Cholesterol (LDL-C) were found in 47.3%, 76.7%, and 41.3% of patients respectively [19].…”
Section: Triacylglycerol/triglyceride Analysismentioning
confidence: 99%